2020
DOI: 10.3390/s20102846
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Lateral Displacement-Based Separation of Magnetic Beads and Its Applications of Antibody Recognition

Abstract: This work presents a magnetic-driven deterministic lateral displacement (m-DLD) microfluidic device. A permanent magnet located at the outlet of the microchannel was used to generate the driving force. Two stages of mirrored round micropillar array were designed for the separation of magnetic beads with three different sizes in turn. The effects of the forcing angle and the inlet width of the micropillar array on the separating efficiency were studied. The m-DLD device with optimal structure parameters shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Since a conventional circular pillar array cannot satisfy user demand in some circumstances, geometric modifications can be made to enhance performance. First, gaps between pillars in two different directions can be adjusted 36 (parametric optimization). Zeming et al demonstrated that an asymmetric DLD gap was able to achieve enhanced separation and throughput of red blood cells 63 .…”
Section: Different Biological Micro-object Separation Microfluidic Sc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since a conventional circular pillar array cannot satisfy user demand in some circumstances, geometric modifications can be made to enhance performance. First, gaps between pillars in two different directions can be adjusted 36 (parametric optimization). Zeming et al demonstrated that an asymmetric DLD gap was able to achieve enhanced separation and throughput of red blood cells 63 .…”
Section: Different Biological Micro-object Separation Microfluidic Sc...mentioning
confidence: 99%
“…Functional molecules include aptamers, antibodies, and other proteins 20 , 30 , 31 . In some cases, magnetic beads are used as labels on biological micro-objects for separation 32 36 . In contrast, label-free microfluidic devices require no functional molecules, and their separation ability depends solely on fluid and particle dynamic properties and fluid-wall interaction properties inside the chip 37 39 .…”
Section: Introductionmentioning
confidence: 99%
“…A multiple separation stage with predesigned arrays (e.g., forcing angle and inlet width) can provide a precise continuous isolation of a wide range of CTCs with different sizes. [ 117 ] In addition, an electro‐optical flow cytometer, for example, processing topographical information (e.g., height profile, and diameter, number, and size distribution, etc.) of cells by using a digital holographic microscopy incorporated into a label‐free µ‐chip, can be incorporated in order to precisely provide the spatial resolution of the texture or inner cellular structure in situ.…”
Section: Label‐free µ‐Chipsmentioning
confidence: 99%